2010
DOI: 10.1258/jhsrp.2009.009095
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing of Health Care Workers in England - A Flawed Policy

Abstract: A new Department of Health policy in England, published in 2007, recommended changes to the pre-employment health checks performed on health care workers before taking up their employment. The policy proposed that all new health care workers should receive immunization against TB and hepatitis B and should be offered testing for hepatitis C and HIV. It also advanced a new requirement that staff who perform exposure-prone procedures must be tested for TB, hepatitis B and C and HIV and must test negative for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Two-thirds of respondents believe HCT should be part of pre-employment medical examination for all prospective health care workers and that they should submit to mandatory HCT, at least once a year. Mandatory HIV testing has been introduced for a large number of HCWs in the developed world (Salkeld & McGeehan, 2010 ). Salkeld, McGeehan, Chaudhuri, and Kerslake ( 2009 ) reported that junior doctors who were offered an HIV test as part of their pre-employment occupational health checks by National Health Service Trusts in the United Kingdom were highly critical of the manner the HIV test was offered.…”
Section: Discussionmentioning
confidence: 99%
“…Two-thirds of respondents believe HCT should be part of pre-employment medical examination for all prospective health care workers and that they should submit to mandatory HCT, at least once a year. Mandatory HIV testing has been introduced for a large number of HCWs in the developed world (Salkeld & McGeehan, 2010 ). Salkeld, McGeehan, Chaudhuri, and Kerslake ( 2009 ) reported that junior doctors who were offered an HIV test as part of their pre-employment occupational health checks by National Health Service Trusts in the United Kingdom were highly critical of the manner the HIV test was offered.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HCWs are uniquely placed in a setting which can provide easy access to testing and advice. Most nursing posts in the NHS, however, do not involve EPPs and there is opposition towards mandatory testing for all new HCWs because of ethical and cost-effectiveness considerations [22]. The main aim of the current guidelines is to protect patients but more could be done to emphasize the benefits to HCWs of an early HIV diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Medical and dental students are also required to undergo additional health clearance before being accepted onto their course. The new guidelines have been criticized,143 and it has been argued that in effect mandatory HIV testing has now been introduced for a large number of HCWs 144…”
Section: Hiv-positive Health Care Workersmentioning
confidence: 99%